Pendampingan Keluarga dengan Kepatuhan Kontrol Berobat pada Penderita ODGJ (Studi di Puskesmas Lawang Malang) - Andika Siswoaribowo; Dhina Widayati; Nisafatus Soniah (Universitas Muhammadiyah Jember, 2022)
Compliance control treatment of patients with ODGJ is important in the healing process. Family assistance is very influential on ODGJ patients in the process of adherence to treatment control and the healing process. The purpose of the study was to determine the relationship between family mentoring and adherence to medication control in patients with ODGJ. The correlational research design uses a cross sectional approach. The population is 112 respondents, purposive sampling technique is 34 respondents. Data collection using a questionnaire scale family assistance (mentoring) and the MMAS instrument for compliance control treatment. The results of the study obtained that almost all of the family assistance provided was in the good category (85.5%), and almost all of the patient's treatment control compliance was in the good category (88.2%). Spearman rank statistical test obtained p-value 0.000 (0.05) and correlation coefficient (r) of 0.879. The relationship of family assistance is related to medication control compliance with a positive and strong direction, so that the better the family assistance, the better the medication control compliance. Mentoring is closely related to compliance with treatment control because it will trigger the patient's spirit to recover, patients feel cared for and control treatment more regularly. It is recommended for families to continue to provide good assistance by providing physical and emotional support, so that it is hoped that ODGJ patients can carry out routine medical control.